A Flexible and Biomimetic Olfactory Synapse with Gasotransmitter‐Mediated Plasticity (Adv. Funct. Mater. 18/2023). (2nd May 2023) - Deng, Yuping; Zhao, Mingyou; Ma, Yuan; Liu, Shangbin; Liu, Mingda; Shen, Boyu; Li, Rongfeng; Ding, He; Cheng, Huanyu; Sheng, Xing; Fu, Wangyang; Li, Zehui; et al.
Abstract : Biomimetic Olfactory Synapses In article number 2214139, Lan Yin and co‐workers propose, a flexible and biomimetic olfactory synapse based on organic electrochemical transistors coupled with breath‐figure derived porous solid polymer electrolytes. The device demonstrates a ppb‐level response limit and desirable selectivity toward hydrogen sulfide, and gas‐mediated synaptic plasticity and typical synaptic behaviors are accomplished.